Los espacios domésticos para la lectura y el atesoramiento de libros: una visión sobre la Zaragoza del barroco - Postiigo Vidal, Juan (Studia Europaea Gnesnensia, 2020)
The intention of this paper is to introduce the reader to the issue of space where one used to read and collect books within the residential structures in seventeenth-century Zaragoza. For this purpose, the author analyzes the inventories of movables, the essential source for studies into aspects of daily life and material culture.